MANAJEMEN KONFLIK PERSPEKTIF PENDIDIKAN ISLAM - YUSNIA BINTI KHOLIFAH (Piwulang: Jurnal Pendidikan Agama Islam, 2019)
Conflict is inevitable and will surely be present in every person's life or the life of an organization. Viewing conflict can be from two angles, each point of view will have different consequences and will even be opposite. When conflicts are seen as positive in the sense that they are seen as learning, conflict will become a force for progress. But on the contrary if the conflict is seen as something that is not good or negative then the conflict will become a weakness that can cause stress, division and even hostility. Looking at these two points of view when someone is told to choose, it will choose the good, that is, conflict is seen positively, because actually everyone does not like division. But this is not easy because in reality everyone tends to be emotional when facing a conflict that ultimately has a negative impact. Therefore we need a way to manage a conflict that comes so that conflict becomes a positive thing. Islamic education teaches various ways on how to deal with conflict. Because in fact there is a difference that is considered as a trigger for the emergence of conflict is a blessing.